“Punk’s Not Dead, It Lives on The Football Terraces”: Tracing The Legacy of Punk in Subcultural Milieu of The Football Firms - Hüseyin Serbes (Medya ve Kültür)
Contrary to the popular perception generated by the mainstream media, the notion of ‘football firm’ has a large subcultural milieu. When this subcultural universe is carefully investigated, an enduring legacy of punk attitude is detected. The center of the punk ethos, which provides a snapshot of the political and cultural landscape, is shaped by some aesthetic codes. This paper attempts to bring together the legacy of punk with the supporter subculture. The study, framed from the perspective of Marxist theory, aims to understand the symbols of resistance of youth subcultures with a micro-sociological perspective by focusing on fanzines within the scope of qualitative research design. With the critical discourse analysis carried out in this context, the modern football phenomenon, which destroys the subjectivity of the fans, is investigated. The findings reveal that Punk’s aggressive, rhetorical and satirical aesthetic codes exist in the stands. The discovery of Punk, which offers a subcultural capital against commodification, alienation and commercialized football, may regenerate the praxis of pleasure, poetry, art, imagination, love and revolution on the football terraces.